KEWIRAUSAHAAN DI PERGURUAN TINGGI MENYIAPKAN ENTREPRENEUR UNGGUL - Margunani, Margunani; Hidayah, Isti; Rosidah, Rosidah (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2015)
Product or service Wira New Business (WUB) generated the students have the advantage of science and technology. Independent entrepreneurs from universities that produce the products / services can be developed through the science and technology-based business consulting to experts, research and laboratories on campus. Readiness is integrated and holistic childbirth entrepreneurs from universities, superior, has a broader and more adaptative insight. Entrepreneurship lecture testruktur, entrepreneurial practices chance divasilitasi Entrepreneurship Student Creativity Program (PKM-K) through a grant to try to try. Student Entrepreneurial Program (PMW) which provide more opportunities, where students who tried because of limited funds got very soft loan (without interest). Useful for students to practice managing capital / funding from outside to study the production, trade, repay, and so on.